Adult onset dystonia: A disorder of the collicular–pulvinar–amygdala network. (October 2021) - Rafee, Shameer; O'Keeffe, Fiadhnait; O'Riordan, Sean; Reilly, Richard; Hutchinson, Michael
Abstract: Models attempting to explain the pathogenesis of adult onset idiopathic focal dystonia often fail to accommodate the entire spectrum of this disorder: the diverse motor and non-motor symptoms, psychiatric and cognitive dysfunction, as well as the sub-clinical, physiological and anatomical, abnormalities. We propose, and present the accumulating evidence, that the adult onset dystonia syndrome is due to disruption in the covert-attentional network, the unconscious sub-cortical mechanism for the detection of potentially environmentally threatening (salient) stimuli, involving the collicular–pulvinar–amygdala network. A critical consideration of this network indicates a number of hypothesis-generated research questions aimed at elucidating the pathogenesis of adult onset dystonia. Given the rarity of adult onset dystonia, international, multidisciplinary, multicentre studies are required to elucidate the prevalence of non-motor symptoms in unaffected relatives, in particular, using temporal discrimination. Research focussing on the non-motor symptoms and the collicular–pulvinar–amygdala pathway may be the key to understanding adult-onset idiopathic focal dystonias (AOIFD) pathophysiology.